Returns, setbacks, and future prospects of bio-energy promotion in northern Ethiopia: the case of family-sized biogas energy - Haftu Etsay Kelebe (Energy, Sustainability and Society, 2018)
Abstract Background Solid biomass-based energy is expected to retain its position as a sole fuel source for households in the rural part of Ethiopia unless alternative energy sources are introduced. Synthesizing small-scale renewable alternative energy sources, such as biogas energy, into the energy mix has become an important strategy to overcome the energy hunger of its rural residents. As part of the government policy, small-scale biogas digesters have been installed in selected districts and regions of the country since 2007. There is, however, limited evidence on whether or not the intended objectives of the domestic biogas initiative have been actualized by the participants of the project. This paper, therefore, intends to investigate the economic benefits of domestic biogas plants along with the challenges facing it and future prospects of the biogas initiative in selected districts of northern Ethiopia. Methods Qualitative data were gathered using focus group discussion and key informant interviews. A survey of 400 households was also administered to capture cross sectional data using structured questionnaires. The qualitative data were analyzed using content analysis. A propensity score matching model was employed to evaluate the effects of domestic biogas technology on energy expenditure, crop yield, and the substitution of chemical fertilizers. Results The study finds that biogas adopters have reduced their monthly energy expenditure on average by 20–36%. Moreover, the existence of a positive crop yield premium of 1.5 quintal/year/household was observed as a result of using bio-slurry as a fertilizer. The key factors that limit the extension of biogas technology to potential biogas adopters are the presence of failed digesters, an inadequate plot of land for the digester construction and a water availability problem. In light of such barriers, however, the study finds that more favorable environments for the widespread use of the technology exist. Conclusions Biogas user households have significantly reduced their energy expenditure compared to non-biogas adopters. Nevertheless, despite the modest increase in crop yield, the overall effect of bio-slurry application on crop productivity and substituting chemical fertilizers was not significant because of an improper bio-slurry utilization and management.